The Cheyenne Indians : their history and lifeways : edited and illustrated - Grinnell, George Bird, 1849-1938; Fitzgerald, Joseph A., 1977- (Library of perennial philosophy. American Indian traditions series., 2008)
Grinell was the long-time editor of Field & Stream magazine and helped to establish both the Yellowstone and Glacier National Parks. During his career he documented several tribes of the old West, including this vivid account of the last of the Cheyenne Indians, who were forced to live out their lives as nomads.